Podhale Palaeogene Flysch as geotouristic attractive region – first look to its unique geological values - Krobicki, Michał; Golonka, Jan (Geotourism/Geoturystyka, 2018)
The primary aim of this paper is note the attention to geological phenomena in the Podhale Flysch region, and especially lithological differentiation of flysch rocks, their sedimentological features, tectonic structures, stratigraphical and palaeontological aspects, and all of these according to recent regional position of Podhale and its palaeogeographical history in wider geodynamic context. Authors summarized the newest knowledge about geological history of the Podhale Flysch region and presented its geotouristic potential in one of the beautiful place in southern Poland. Short reviews of several aspects of geological works have been made according to: sedimentology, biostratigraphy, petrography and mineralogy, structural geology, organic geochemistry, palaoentology and palaeoecology, palaeogeography and basin analysis, geophysics, geothermy, Quaternary geology and geomorphology, inanimate nature protection and geotourism. In fact, the Podhale Flysch region is good place for geological education and promotion of Earth sciences. // Podstawowym celem niniejszej pracy jest zwrócenie uwagi na geologiczne fenomeny f liszu podhalańskiego, a szczególnie zróżnicowanie utworów fliszowych regionu, ich sedymentologicznych cech, struktur tektonicznych, aspektów stratygrafii i paleontologii, a one wszystkie w nawiązaniu do dzisiejszej, regionalnej pozycji Podhala i jego paleogeograficznej historii w szerszym geodynamicznym kontekście. Autorzy podsumowali najnowszą wiedzę na temat geologicznej historii fliszu podhalańskiego i zaprezentowali jego geoturystyczny potencjał w jednym z najpiękniejszych miejsc Polski południowej. Przedstawiono krótki przegląd wielu aspektów prowadzonych tutaj prac geologicznych z: sedymentologii, biostratygrafii, petrografii i mineralogii, geologii strukturalnej, geochemii organicznej, paleontologii i paleoekologii, paleogeografii i analizy basenów, geofizyki, geotermii, geologii czwartorzędu i geomorfologii, ochrony przyrody nieożywionej i geoturystyki. Zdecydowanie, rejon fliszu podhalańskiego jest dobrym miejscem dla edukacji geologicznej i promocji nauk o Ziemi.